Monaci scrittori San Salvatore al Monte Amiata tra Impero e Papato (secoli VIII-XIII) - MARROCCHI, Mario (Reti Medievali E-Book, 2014)
The royal monastery of San Salvatore on Mount Amiata, which, according to tradition, was founded in the 8th century by the will of the Lombard kings near the papal lands, has been the focus of numerous researches in recent decades dedicated not only to some famous codices preserved for centuries in his library, but also to the documentary writings handed down in the Diplomatico, which collects documentation from the mid-eighth century. In this volume, the paleographic and diplomatic interpretation of the writings elaborated by the abbots and the Amiata monks intertwines with the reconstruction of the practices of power management, both in its local dimension and in that of relations with popes and emperors.